2021
DOI: 10.1007/s00296-021-04799-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of patients with rheumatoid arthritis about self-assessment of disease activity after watching an educational video: a qualitative pilot study from the AUTO-DAS in Middle Eastern Arab countries project

Abstract: To evaluate the perceptions of patients with rheumatoid arthritis (RA) about self-assessment of their disease activity after watching an educational video. Consecutive patients with RA consulting their rheumatologist in six Middle Eastern Countries were invited to watch an educational video developed to teach self-assessment using Disease Activity Score (DAS-28). Then, a rheumatology nurse conducted a semi-structured interview and collected the patients’ perception about the understanding of the video, feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Of these 29 studies, 13 were categorised as having low risk of bias,36–48 10 were categorised as having moderate risk of bias,49–58 and 6 were unable to be assessed due to a lack of detailed evaluation of the developed approaches 59–64. The raw scores of these studies were shown in online supplemental file 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these 29 studies, 13 were categorised as having low risk of bias,36–48 10 were categorised as having moderate risk of bias,49–58 and 6 were unable to be assessed due to a lack of detailed evaluation of the developed approaches 59–64. The raw scores of these studies were shown in online supplemental file 3.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies included in the synthesis, 16 focused on cancer,36–42 49–54 59–61 5 on respiratory diseases,43 44 55 62 63 3 on cardiovascular diseases45 46 64 and 1 each on other health conditions including concussion,56 labour,57 malaria,47 neonatal illness48 and RA 58. Six were community-based studies engaging various parties (eg, educators and women leaders) in the communities and employing different outreach efforts (eg, flyers and radio advertisements),37 39 47 52 61 64 among which two involved training of both laypersons and health providers 47 64.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians can also send a brochure or video tutorial regarding the maneuvers that will be performed for the physical examination to the patient, before the teleconsultation [23][24][25][26][27]. It is recommended to translate and validate such tutorials in Arabic, with adaptation to local dialects where appropriate [23,28].…”
Section: Patients Should Have a Choice Of Their Provider Of Medical Teleconsultationmentioning
confidence: 99%
“…[25][26][27][28][29] It is recommended to translate and validate such tutorials in Arabic, with adaptation to local dialects where appropriate. [25,30] BPS 6: Patient-reported outcomes (LoE 3; LoA 7.73; Consensus 100%)…”
Section: General Principlesmentioning
confidence: 99%